Normes, exceptions et variabilité : manifestations de profils conatifs dans les activités d’apprentissage de l’anglais - Denyze Toffoli (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
Initially intended to present an analysis of learner profiles and their manifestations in specific learner trajectories, the present article adopts a critical stance with regards to such an undertaking and opts for a mixed-methods approach which favours informed ethnographic story-telling as a means to better understanding learner interaction with other-language resources both in and out of the classroom.